2017
DOI: 10.1002/2211-5463.12182
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐catenin participates in dialysate‐induced peritoneal fibrosis via enhanced peritoneal cell epithelial‐to‐mesenchymal transition

Abstract: Long‐term exposure to peritoneal dialysate with high glucose (HG) leads to peritoneal fibrosis and thus decreases dialysis efficiency. In this study, we explored the role of β‐catenin in this process. C57BL/6 mice received daily intraperitoneal injection with 10% of the body weight of saline (control), 4.25% glucose peritoneal dialysis fluid (PDF), or PDF combined with 5 mg·kg −1 of the β‐catenin inhibitor ICG‐001 (PDF+ICG) for 30 days. Also, mice peritoneal epithelial cells (mPECs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
3
15
1
Order By: Relevance
“…We used Dickkopf‐related protein (DKK‐1) to inhibit WNT/β‐catenin signalling and observed a decrease in both angiogenesis and also epithelial to mesenchymal transition (EMT) . In a similar study of dialysis infused peritoneal fibrosis, β‐catenin was shown to induce EMT . Our results concur with reports of WNT signalling in other fibrotic diseases …”
Section: Introductionsupporting
confidence: 92%
“…We used Dickkopf‐related protein (DKK‐1) to inhibit WNT/β‐catenin signalling and observed a decrease in both angiogenesis and also epithelial to mesenchymal transition (EMT) . In a similar study of dialysis infused peritoneal fibrosis, β‐catenin was shown to induce EMT . Our results concur with reports of WNT signalling in other fibrotic diseases …”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, Ppar-γ, a nuclear receptor which is associated with PSC quiescence [4,22,25,26], is known to have anti-inflammatory/anti-fibrotic activity [36] and should compete with β-catenin for binding to CBP's N-terminal region, thereby phenocopying ICG-001 antagonism of CBP/β-catenin binding and associated signaling [37]. As such, it is not surprising that various studies have shown that treatment with CBP/β-catenin antagonist ICG-001 (or the structurally related derivative PRI-724) is effective pre-clinically at ameliorating fibrosis in the peritoneum [38], endometrium [39], lung [13], kidney [32], skin [40], heart [41], and liver [19,42]. Importantly, a recent phase 1 trial utilizing PRI-724 demonstrated that treatment of patients safely improved liver histology and Child-Pugh scores for cirrhosis [43], suggesting that CBP/β-catenin antagonism is a viable therapeutic for combating fibrotic diseases in general.…”
Section: Discussionmentioning
confidence: 99%
“…Although TGF-β1 and/or the renin-angiotensin system are the classical mediators of peritoneal fibrosis, recent reports have revealed the significance of other signaling pathways in peritoneal fibrosis [2428]. Ji et al [25] investigated the role of β-catenin, a cytoskeletal protein, in high-glucose dialysate-induced EMT pathology. They found that inhibiting β-catenin reversed the expression of high-glucose-induced EMT markers.…”
Section: Discussionmentioning
confidence: 99%